2022
DOI: 10.1371/journal.pbio.3001912
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic sulfur fixation via a new homocysteine synthase allows yeast cells to cooperatively compensate for methionine auxotrophy

Abstract: The assimilation, incorporation, and metabolism of sulfur is a fundamental process across all domains of life, yet how cells deal with varying sulfur availability is not well understood. We studied an unresolved conundrum of sulfur fixation in yeast, in which organosulfur auxotrophy caused by deletion of the homocysteine synthase Met17p is overcome when cells are inoculated at high cell density. In combining the use of self-establishing metabolically cooperating (SeMeCo) communities with proteomic, genetic, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 51 publications
3
21
0
Order By: Relevance
“…This indicated that we were not merely observing residual growth fueled by organosulfurs that the cells had accumulated during exponential growth in methionine-supplemented medium. Similar observations have since been reported by other labs [24,25], and chromatographic analyses has confirmed that organosulfur contaminants occur in negligible quantities in the commercially available yeast nitrogenous base that was used to prepare SD medium [25].…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…This indicated that we were not merely observing residual growth fueled by organosulfurs that the cells had accumulated during exponential growth in methionine-supplemented medium. Similar observations have since been reported by other labs [24,25], and chromatographic analyses has confirmed that organosulfur contaminants occur in negligible quantities in the commercially available yeast nitrogenous base that was used to prepare SD medium [25].…”
Section: Resultssupporting
confidence: 86%
“…Indeed, while met17∆ grew in a density-dependent fashion ( indicating that the inability of met17∆yll058w∆ to grow on sulfate did not result from impairments in sulfide release but from defects in sulfide assimilation. While we were investigating this phenomenon, two other groups simultaneously reported this sulfide-assimilation function of YLL058W [24,25], and Yu et.al. named the locus Hydrogen Sulfide Utilizing-1 (HSU1) [25].…”
Section: Hsu1 Is Required For Sulfide Assimilation In Met17∆mentioning
confidence: 78%
See 2 more Smart Citations
“…Furthermore, endogenous hydrogen sulfide (H 2 S) production, as part of the organic sulfur cycle, 79 is essential for the beneficial effects of dietary restriction 80 and has been shown to provide health benefits in experimental organisms, ranging from protection from ischemia/reperfusion injury to lifespan extension. 81 In yeast, H 2 S extends CLS in a temporally resolved manner, 82 and a recent study in our lab found that MET15 auxotrophs generate increased levels of H 2 S, 83 hence it is possible that increased levels of H 2 S also occur in SeMeCo and participate in the protective role of the self-generated exometabolome.…”
Section: Ll Open Accessmentioning
confidence: 81%